(untitled) (Research, Society and Development, 2021)
This study aimed to assess the knowledge of teachers about Team-Based Learning (TBL) and the factors that hinder its implementation in undergraduate medicine. This was a quantitative, cross-sectional and descriptive study using a questionnaire. The results obtained showed that 31.25% of the professors reported not knowing how many steps were recommended in the TBL, and among the others who answered knowing, 72.72% answered incorrectly. When questioning what the steps are, 34.37% of the teachers said they were not aware, whereas among the respondents, 80.95% were incorrect. Finally, with regard to the time allocated to each of the stages, 68.75% did not know how to answer and 80% of those who said they knew were mistaken. Among the hindering factors for implementing TBL activities in teaching practice, the lack of professional qualification (96.875%), plus the scarcity of works on the subject (81.25%), stood out. It is concluded that practically all the participants did not know it or had misconceptions about the use of TBL, the lack of professional qualification being the main factor hindering this process.